Participation in Sport, Empowerment, and Safety From Violence: Critiquing the Connections Through Women’s Experiences in Aotearoa/New Zealand - Armstrong, Lynzi (Violence against women, 2022)
Men’s violence against women is a global issue, and in recent decades its relationship with sport has been examined. Much research has focused on male athletes as perpetrators, seeking to understand how sport may foster misogynistic behavior. However, paradoxically, recent research has also examined women’s involvement in sport as a protective factor against gendered violence. This article explores this, drawing on the perspectives of 20 women. We argue that sport was experienced in contradictory ways, and thus, positioning women’s involvement in sport as a protective factor obscures complex experiences and reinforces the narrative that women are responsible for their safety.